ORAL HEALTH LITERACY OF CADRES ON MATERNAL ORAL HEALTH BEFORE AND DURING PREGNANCY - Mahirawatie, Ida Chairanna; Astuti Ngurah Putri, I Gusti Ayu Kusuma (Faculty of Vocational Studies, Universitas Airlangga, 2024)
Background: Dental health problems frequently encountered in pregnant women, which require immediate treatment, include gingivitis gravidarum, periodontitis, epulis gravidarum, and caries. One of the prevention efforts for these disorders is to provide assistance to mothers before and during pregnancy. This assistance can be done by empowering health cadres. It is necessary to have community empowerment cadres in the health sector. Purpose: This study aims to determine the influence of oral health literacy of cadres in delivering information on maternal oral health efforts before and during pregnancy. Method: This study employed a quasi-experimental research design. The total of samples taken in this research was 70 people. The sampling method used a purposive sampling technique. The research sample was divided into two groups, namely the control group and the treatment group. Both groups were given a pre-test. Following the pre-test, the treatment group received cadre training. Both groups were then asked to complete a post-test at the end. Data were collected using the questionnaire. Result: The p-value was 0.000 < 0.05, indicating a significant difference in the mean oral health literacy values between the treatment group and the control group. Conclusion: There is a significant difference in the value of oral health literacy and maternal dental health efforts before and during pregnancy.